HIV-1 conserved mosaics delivered by regimens with integration-deficient, DC-targeting lentiviral vector induce robust T cells - Hanke, T; Wee, E; Ondondo, B; Berglund, P; Archer, J; McMichael, A; Baltimore, D; ter Meulen, J (Elsevier, 2016)
To be effective against HIV-1, vaccine-induced T cells must selectively target epitopes, which are functionally conserved (present in the majority of currently circulating and reactivated HIV-1 strains) and, at the same time, beneficial (responses to which are associated with better clinical status and control of HIV-1 replication), and rapidly reach protective frequencies upon exposure to the virus. Heterologous prime-boost regimens using virally vectored vaccines are currently the most promising vaccine strategies, nevertheless, induction of robust long-term memory remains challenging. To this end, lentiviral vectors induce high frequencies of memory cells due to their low-inflammatory nature, while typically inducing only low antivector immune responses. Here, we describe construction of novel candidate vaccines ZVex.tHIVconsv1 and ZVex.tHIVconsv2, which are based on an integration-deficient lentiviral vector platform with preferential transduction of human dendritic cells and express bivalent mosaic of conserved-region T-cell immunogens with a high global HIV-1 match. Each of the two mosaic vaccines was individually immunogenic. When administered together in heterologous prime-boost regimens with chimpanzee adenovirus and/or poxvirus MVA vaccines to BALB/c and outbred CD1-Swiss mice, they induced median frequency of over 6,000 T-cells/10^6 splenocytes, which were plurifunctional, broadly specific and cross-reactive. These results support further development of this vaccine concept.